Implementation of Cianjur Culture Pillars in Mathematical Multiliteration Assisted Smartphone Technology (Geogebra Android Version) to Increase Higher Order Thinking Skill (HOTS) Skill Vocational School Students - Carel, Gustaf; Sugiarni, Rani; Alghifari, Egi; Yastrib, Harum (PRISMA, 2018)
This research aims to know the influence of the implementation of the cultural cornerstones of Cianjur in Learning Mathematical Multiliterasi Berbatuan Smartphone Technology Uses an Android version of Geogebra Applications To enhance the capabilities of Higher Order Thinking Skills (HOTS) Mathematically Vocational School. The design used The Static-Group Pretest-Posttest Design. For class experiments given treatment that is by learning the android version of geogebra-assisted multiliterasi, and grade control get the conventional learning. The population of this research is the class X OTKP SMK Al Madina Cianjur 30 students with samples is then divided into two groups, the experimental class and the class of the control. First data collection with the instrument test and question form. Data analysis using the test of normality, test its homogeneity, test safety/difference of two averages, percentage values and attitudes. Results of the study indicate that there is an increase in the ability of the students with learning multiliterasi HOTS mathematically better than conventional learning. And positive student attitudes of learning by implementing the cultural pillars cianjur.